Penyuluhan Kebijakan Era Normal Baru Sebagai Upaya Pencegahan Penularan Covid-19 Di Kecamatan Kamal - Rina Yulianti (Jurnal Ilmiah Pangabdhi, 2021)
Government has issued Presidential Decree No. 11 of 2020 concerning the Determination of Covid-19 Public Health Emergencies, PERPU No. 1 of 2020 concerning State Financial Policies and Financial System Stability for Handling the Covid-19 Pandemic, as well as PP No. 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating the Handling of Covid-19. It is our collective responsibility to support government policies in dealing with health emergencies and prevention. Unfortunately, the community sometimes does not realize the importance of supporting government policies and programs. The purpose of this service grant is to increase public legal awareness of the obligation to comply with health protocols which are the basis for the new normal era and also provide learning to prevent the transmission of corona virus 19 Based on the Decree of the Minister of Health of the Republic of Indonesia Number Hk.01.07 / Menkes / 382/2020 concerning Health Protocols for Communities in Public Places and Facilities in the Context of Prevention and Control of Corona Virus Disease 2019 (Covid-19). Legal counseling methods are used to disseminate various government policies in accordance with Article 1 paragraph 1 of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number: M.01-PR.08.10 of 2006 concerning the Pattern of Legal Counseling. Indirect counseling activities were carried out by distributing banners on each of the hamlet's main roads, installing x-banners at public service offices, distributing masks and spraying disinfectants in public service and worship places. This new normal era behavior policy counseling has provided knowledge and changed the pattern of people's attitudes in their activities during the Covid-19 pandemic. Law enforcement to implement this government policy needs to be supported by the authorized parties and the active village government in carry out socialization.